1978
DOI: 10.1515/znc-1978-5-610
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Benzoic Acids and Phenols in Cell Suspension Cultures of Soybean and Mung Bean

Abstract: Uptake of benzoic and salicylic acid by soybean cell suspension cultures is diffusion-mediated and exclusively leads to glucose-esters. - Veratric acid is para-demethylated to vanillic acid which is conjugated to a monoglucoside. - Nitrobenzoic acids are scarcely taken up by cell cultures with glucose-esters as sole products. - Ring-labelled derivatives of vanillylalcohol and creosol are mainly polymerized to insoluble structures, ring cleavage reactions could not be observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

1981
1981
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
1
7
2
Order By: Relevance
“…In this report, the metabolism of SA to glucose conjugates and the vacuolar localization of these glucose conjugates are described. In contrast to a previous report that indicated that [ 14 C]SA supplied to soybean cells was converted only to SGE (Barz et al 1978), we have been able to demonstrate that SAG is the major metabolite of SA formed in soybean along with lower levels of glucosylated 2,5‐DHBA and MeSA 2‐ O ‐β‐ d ‐glucose. In addition, we have provided the first direct evidence that the glucose conjugates of SA are localized in the vacuole and that the SAGT activity that forms SAG is located outside the vacuole.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this report, the metabolism of SA to glucose conjugates and the vacuolar localization of these glucose conjugates are described. In contrast to a previous report that indicated that [ 14 C]SA supplied to soybean cells was converted only to SGE (Barz et al 1978), we have been able to demonstrate that SAG is the major metabolite of SA formed in soybean along with lower levels of glucosylated 2,5‐DHBA and MeSA 2‐ O ‐β‐ d ‐glucose. In addition, we have provided the first direct evidence that the glucose conjugates of SA are localized in the vacuole and that the SAGT activity that forms SAG is located outside the vacuole.…”
Section: Introductioncontrasting
confidence: 99%
“…The majority of the SA found in untreated and tobacco mosaic virus (TMV)‐inoculated leaves of tobacco ( Nicotiana tabacum L. ‘Xanthi‐nc’ NN genotype) was thought to exist primarily as SAG (Enyedi et al 1992, Malamy et al 1992); however, subsequent research revealed that small amounts of SGE could also be formed (Edwards 1994, Lee and Raskin 1998). In soybean cell suspension cultures, SA was reported to be exclusively metabolized to SGE (Barz et al 1978) and in a variety of other plant species SA was metabolized primarily to the 5‐ O ‐glucoside of gentisic acid (Cooper‐Driver et al 1972, Schulz et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The question arises as to why the inhibitory effect of SA on ethylene production only lasted for 5 h . One possibility is that SA is readily conjugated and/or degraded in rice leaf cells [2,7] . The present investigation demonstrated that SA inhibited the conversion of ACC to ethylene in rice leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Their fate in the environment and their sensitivity to degradation systems in plants are determined by the nature of the substituents carried by their aromatic ring. Earlier studies have shown that plants, like microorganisms (Gottschalk, 1979), are able to degrade benzene by several pathways including oxidative cleavage of the aromatic ring and incorporation of the resulting products in the cell regular metabolism (Durmishidze and Ugrekhelidze, 1969;Barz et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Ever since numerous literary data prove uptake and mineralization of benzene or its derivatives by higher plants (Ferro et al, 1997;Ugrekhelidze et al, 1997; see for review Korte et al, 2000). However, evidence for ring cleavage of aromatic compounds in plants is scarce.…”
Section: Introductionmentioning
confidence: 99%